1972
DOI: 10.1103/physrevd.6.3641
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation in aφ3-Theory Ladder Model

Abstract: We study the inclusive reaction a + b -c + (anything), where all the particles belong to a single scalar field @ ( x ) interacting through a g @~~( x ) term. We do this in a ladder model for the forward a b c -abE process, whose amplitude is intimately related to the inclusive distribution. The choice of the infinite sequence of ladder diagrams as well as the assumptions involved are natural extensions of analogous work in the literature for four-point functions.In the fragmentation limit, the model yields the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In comparison to this interaction the direct interaction which decays exponential [12] can be neglected. We stress that the leading asymptotic term of the x dependence of u(x) is determined by the quartic anharmonicity only.…”
Section: By'mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to this interaction the direct interaction which decays exponential [12] can be neglected. We stress that the leading asymptotic term of the x dependence of u(x) is determined by the quartic anharmonicity only.…”
Section: By'mentioning
confidence: 99%
“…In case of one dimension all analytical results concerning the dynamics of the domain walls (multikink dynamics) were obtained in the framework of an ideal-gas phenomenology [2][3][4]6,9]. There, the direct interaction between kinks does not play a crucial role due to its exponential decay [12]. Furthermore it was shown that the kink-phonon interaction results in a renormalization of either the phonon density of states [3] or the kink density [6].…”
mentioning
confidence: 99%